Parameter Studies on High-Velocity Oxy-Fuel Spraying of CoNiCrAlY Coatings Used in the Aeronautical Industry - Cabral Miramontes, José Ángel; Gaona Tiburcio, Citlalli; Almeraya Calderón, Facundo; Estupiñan López, Francisco Humberto; Pedraza Basulto, G. K.; Poblano Salas, Carlos (Hindawi Publishing Corporation, 2014)
The thermal spraying process is a surface treatment which does not adversely affect the base metal on which it is performed. The coatings obtained by HVOF thermal spray are employed in aeronautics, aerospace, and power generation industries. Alloys and coatings designed to resist oxidizing environments at high temperatures should be able to develop a surface oxide layer, which is thermodynamically stable, slowly growing, and adherent. MCrAlY type (M = Co, Ni or combination of both) coatings are used in wear and corrosion applications but also provide protection against high temperature oxidation and corrosion attack in molten salts. In this investigation, CoNiCrAlY coatings were produced employing a HVOF DJH 2700 gun. The work presented here focuses on the influences of process parameters of a gas-drive HVOF system on the microstructure, adherence, wear, and oxygen content of CoNiCrAlY. The results showed that spray distance significantly affects the properties of CoNiCrAlY coatings.